A personalized approach in education: problems and prospects - Laura Kh. Urusova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the modern education system, one of the strategic priorities is the theoretical and methodological understanding and practical implementation of personality-oriented learning. The paper considers the problem of implementing a personified approach in the process of education and training. The author's vision of a personality-oriented approach is stated. Some theses of psychology and pedagogy are studied to build the concept of an individual approach in education and training. The author tried to develop a mechanism for the implementation of a personality-oriented approach in teaching a foreign language in a higher educational institution. The study made it possible to argue that in the psychological and pedagogical science there is currently a wide range of conceptual approaches to solving this problem. However, common feature is the emergence as a subject of the learner personality, creating the necessary conditions for his full learning and development. The initial assumption was confirmed by the study that the implementation of personality-oriented learning will be possible if this process is designed as a joint learning and cognitive activity of the learner and learner, aimed at the harmonious and comprehensive development of the learner.